Emotion control: key to successfull decisions - Villavicencio Araníbar, Jorge A. (2020)
Modern management shows that one of the foundations on which organizational results rest is people, and everything that surrounds them within a group: values, mission, vision, organizational culture, ethics, etc. Under this logic, for companies, it becomes imperative that their human resources, as a whole, develop all the potential they have, in a favorable and ideal environment, for the achievement of the objectives that the organization sets; but it is even more important that these people get to know each other internally, so that, through the so-called “soft skills”, they facilitate this achievement of objectives. This essay focuses on these issues, combining theoretical arguments on emotions, with proposals based on actual professional work experience.